Sistema psichologiceskogo soprovozdenija sportivnoj dejatel'nosti - Sivickij, V. G. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
In the article there are stated the basic directions of the activity of a sports psychologist which can be effectively realized only at a corresponding organizational support and qualification of experts. In practice there are no perfect conditions, and the psychologist should solve on his way a great number of different problems.